Political magic - Loar, Christopher F. (Fordham University Press, 2014)
Introduction: magical government – Enchanting the savage: the politics of pyrotechnics in the Cavendish Circle – Fire and sword: Aphra Behn and the materials of authority – Talking guns and savage spaces: Daniel Defoe's civilizing technologies – Doctrines détestables: Jonathan Swift, despotism, and virtue – Savage vision: violence, reason, and surveillance in Eliza Haywood – Coda: Enemies
9780823256914
Keywords: Political fiction; English; English fiction; Politics and literature; Politics in literature; Authority in literature; Aliens in literature